Religion and the Android - Clocksin, William F. (Zygon, 2024)
Future developments in artificial intelligence may take the form of androids, humanlike robots that people accept as persons and equals in society. Such androids would not be designed to imitate humans but would make their own claim at nonhuman personhood through engagement in a variety of relationships over long periods of time, thus developing an existence marked by meaning and purpose. For humans, religion historically has been a tool for understanding our place in the world and our relationships with others—human, nonhuman, or supernatural. Androids might also need a form of religious reasoning to operate fluently in the world and understand their role in it and their relationship with other persons, tangible or intangible. Authentic personhood requires meaning to be born from interdependence, so the intelligent android that comes to acknowledge its interdependence with others may eventually be called to acknowledge its dependence upon divine others and what we humans term the gifts of grace.